Crystallized indium tin composite oxide film, transparent conductive film and method for producing the same
By using crystallized indium tin composite oxide film with a thickness of more than 35 nm and grains with an average particle size of more than 110 nm in the transparent conductive film, the problem of reducing chemical resistance when thickening is solved, and low surface resistance and excellent chemical resistance are achieved.
Patent Information
- Application Number
- CN202080046631.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-27
- Filing Date
- 2020-06-12
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2040-06-12
AI Technical Summary
When the existing transparent conductive film thickens, the average grain diameter becomes smaller, resulting in a decrease in chemical resistance.
A crystalline indium tin composite oxide film with a thickness of 35 nm or more was used to contain crystal grains with an average particle size of 110 nm or more, and an amorphous indium tin composite oxide film was sputtered on one surface of the thickness direction of the transparent film substrate, and then a crystalline indium tin composite oxide film was formed by heating.
Low surface resistance and excellent chemical resistance are achieved, while the film performance is further optimized by controlling the proportion of tin oxide and the roughness of the film substrate.
Smart Images

Figure CN114040842B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a crystallized indium tin composite oxide film, a transparent conductive thin film and a method for producing the same, and more particularly to a crystallized indium tin composite oxide film, a transparent conductive thin film having the same and a method for producing the same. Background Art
[0002] Conventionally, transparent conductive films are known that include a crystalline transparent conductive film containing indium oxide as a main component on a transparent plastic film substrate. The crystalline transparent conductive film generally contains a plurality of grains.
[0003] For example, a transparent conductive film having a thickness of 20 nm and an average crystal grain diameter (average grain size of crystal grains) of 130 nm has been proposed (for example, refer to Example 6 of Patent Document 1 listed below).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-28275 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] In recent years, transparent conductive films have been required to have lower surface resistance, and attempts have been made to increase the thickness of transparent conductive films.
[0009] However, when the transparent conductive film becomes thicker, the average crystal grain size becomes smaller, which disadvantageously reduces the chemical resistance.
[0010] The present invention provides a transparent conductive film having low surface resistance and excellent chemical resistance and a method for producing the same.
[0011] Solutions for solving problems
[0012] The present invention (1) comprises a crystallized indium tin composite oxide film having a thickness of 35 nm or more, the crystallized indium tin composite oxide film containing crystal grains having an average particle size of 110 nm or more.
[0013] The crystallized indium tin composite oxide film has a thickness of 35 nm and therefore has a low surface resistance.
[0014] In addition, the crystallized indium tin composite oxide film has excellent chemical resistance because it includes crystal grains having a relatively large average grain size of 110 nm or more.
[0015] Therefore, the crystallized indium tin composite oxide film has low surface resistance and excellent chemical resistance.
[0016] The present invention (2) comprises the crystallized indium tin composite oxide film according to (1), which comprises a region in which the proportion of tin oxide is 8 mass % or more.
[0017] The surface resistance of the crystallized indium tin composite oxide film can be reduced.
[0018] The present invention (3) includes a transparent conductive film comprising: a transparent film substrate; and the crystallized indium tin composite oxide film according to (1) or (2) disposed on one surface in the thickness direction of the film substrate.
[0019] Since the transparent conductive thin film includes the above-mentioned crystallized indium tin composite oxide film, it has low surface resistance and excellent chemical resistance.
[0020] The present invention (4) comprises the transparent conductive film described in (3), wherein the one surface in the thickness direction of the transparent film substrate has an arithmetic mean roughness Ra of 1.0 nm or less.
[0021] In the transparent conductive film, one surface in the thickness direction of the transparent film substrate has a small arithmetic mean roughness Ra of 1.0 nm or less, so that the hindrance of crystal growth in the amorphous indium tin composite oxide film disposed on one surface in the thickness direction of the transparent film substrate can be suppressed. Therefore, crystal grains with a large average particle size can be formed in the crystallized indium tin composite oxide film. As a result, the crystallized indium tin composite oxide film of the transparent conductive film has excellent chemical resistance.
[0022] The present invention (5) includes a method for manufacturing a transparent conductive film, which is a method for manufacturing the transparent conductive film described in (2) or (3), the manufacturing method comprising: a first step of sputtering one surface in the thickness direction of the transparent film substrate to form an amorphous indium tin composite oxide film; and a second step of heating the amorphous indium tin composite oxide film to form a crystallized indium tin composite oxide film, wherein in the first step, the sputtering is carried out in the presence of an inert gas with a partial pressure of 0.4 Pa or more.
[0023] In the first step of the method for producing the transparent conductive film, sputtering is performed in the presence of an inert gas with a high partial pressure of 0.4 Pa or more, so that crystal grains with a large average particle size can be formed. As a result, a transparent conductive film having a crystallized indium tin composite oxide film with excellent chemical resistance can be produced.
[0024] Effects of the Invention
[0025] The crystallized indium tin composite oxide film obtained by the production method of the present invention has low surface resistance and excellent chemical resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a cross-sectional view of one embodiment of the crystallized indium tin composite oxide film and the transparent conductive thin film of the present invention.
[0027] Figure 2 for Figure 1 2 is a cross-sectional view of a modified example of the transparent conductive film shown.
[0028] Figure 3 middle, Figure 3 A~ Figure 3 B is an image processing diagram of the SEM photograph used in the evaluation of the example, Figure 3 A represents Example 1, Figure 3 B represents Comparative Example 2. DETAILED DESCRIPTION
[0029] <One Implementation Method>
[0030] [Crystallized Indium Tin Composite Oxide Film]
[0031] One embodiment of the crystallized indium tin composite oxide film of the present invention will be described.
[0032] The crystallized indium tin composite oxide film has one surface and the other surface facing each other in the thickness direction. The crystallized indium tin composite oxide film has a film shape extending in a plane direction perpendicular to the thickness direction.
[0033] The thickness of the crystallized indium tin composite oxide film is 35 nm or more. If the thickness of the crystallized indium tin composite oxide film is less than the above lower limit, the surface resistance of the crystallized indium tin composite oxide film cannot be reduced.
[0034] The thickness of the crystallized indium tin composite oxide film is preferably 38 nm or more, more preferably 40 nm or more, further preferably 45 nm or more, particularly preferably 50 nm or more, most preferably 55 nm or more, further preferably 60 nm or more, 70 nm or more, 80 nm or more, 100 nm or more, 125 nm or more, and 150 nm or more. When the thickness of the crystallized indium tin composite oxide film is greater than the above lower limit, the surface resistance of the crystallized indium tin composite oxide film can be sufficiently reduced.
[0035] Note that, from the viewpoint of reducing the surface resistance of the crystallized indium tin composite oxide film, the upper limit of the thickness of the crystallized indium tin composite oxide film is not particularly limited. The thickness of the crystallized indium tin composite oxide film is usually 1000 nm or less, and 500 nm or less.
[0036] The crystallized indium tin composite oxide film contains grains. Figure 3The symbol 9 in A of ) exists in plurality in the crystallized indium tin composite oxide film. In addition, the plurality of crystal grains exist, for example, throughout the entire surface direction and the entire thickness direction of the crystallized indium tin composite oxide film. The plurality of crystal grains are respectively formed by grain boundaries (refer to Figure 3 The symbol of A is divided into 10).
[0037] The average grain size of the crystal grains is 110 nm or more.
[0038] It should be noted that the average particle size of the crystal grains is the average particle size of the crystal grains when one surface in the thickness direction of the crystallized indium tin composite oxide film is observed by SEM, and the details of the measurement method are described in detail in the following Examples.
[0039] Reference Figure 3 When the average grain size of the crystal grains 9 is less than the above lower limit, the occupancy rate per unit area of the grain boundaries 10 of the crystallized indium tin composite oxide film 1 increases excessively. In this case, when one surface in the thickness direction of the crystallized indium tin composite oxide film 1 is exposed to liquid chemicals and the above-mentioned grain boundaries 10 become the entrance of the chemical invasion path, the occupancy rate per unit area of the entrance also increases, so that the chemical resistance is significantly reduced.
[0040] The average particle size of the crystal grains is preferably 130 nm or more, more preferably 150 nm or more, further preferably 170 nm or more, particularly preferably 200 nm or more, most preferably 250 nm or more, and further preferably 300 nm or more, 400 nm or more, and 450 nm or more. When the average particle size of the crystal grains is greater than the above lower limit, the reduction in chemical resistance of the crystallized indium tin composite oxide film can be sufficiently suppressed.
[0041] The material of the crystallized indium tin composite oxide film is crystalline indium tin composite oxide (ITO). ITO is a composite oxide containing indium (In) and tin (Sn) as essential components. Specifically, ITO contains tin oxide (SnO 2 ) and indium oxide (In 2 O 3 ) as the main component.
[0042] The content ratio of tin oxide relative to the total amount of tin oxide and indium oxide is, for example, 0.5 mass % or more, preferably 3 mass % or more, more preferably 5 mass % or more, further preferably 8 mass % or more, particularly preferably 9 mass % or more, and, for example, 20 mass % or less, preferably 15 mass % or less.
[0043] When the content of tin oxide is greater than or equal to the above lower limit, the surface resistance of the crystallized indium tin composite oxide film can be reduced. When the content of tin oxide is less than or equal to the above upper limit, the strength of the crystallized indium tin composite oxide film is excellent.
[0044] The content ratio of indium oxide is the remainder of the content ratio of tin oxide in the above-mentioned total amount. It should be noted that ITO may also contain additional components other than the main component (essential component), specifically, additional components such as Zn, Ga, Sb, Ti, Si, Zr, Mg, Al, Au, Ag, Cu, Pd, W, Fe, Pb, Ni, Nb, Cr, and Ga.
[0045] The crystallized indium tin composite oxide film may include a region where the proportion of tin oxide is 8 mass % or more. When the crystallized indium tin composite oxide film includes a region where the proportion of tin oxide is 8 mass % or more, the surface resistance of the crystallized indium tin composite oxide film can be reduced.
[0046] For example, the crystallized indium tin composite oxide film includes a first region (reference symbol 11) as an example of a region in which the proportion of tin oxide is 8% by mass or more and a second region (reference symbol 12) in which the proportion of tin oxide is lower than the proportion of tin oxide in the first region. Specifically, the crystallized indium tin composite oxide film sequentially includes a layered first region and a layered second region arranged on one surface in the thickness direction of the first region. It should be noted that the boundary between the first region and the second region is allowed to be unconfirmed and unclear through observation using a measuring device. It should be noted that the crystallized indium tin composite oxide film may have a concentration gradient in which the concentration of tin oxide gradually increases from one surface to the other surface in the thickness direction. When the crystallized indium tin composite oxide film includes a second region on the basis of the above-mentioned first region, the desired crystallization rate can be obtained by adjusting the ratio of the regions.
[0047] The ratio of tin oxide in the first region is preferably 9 mass % or more, more preferably 10 mass % or more, and is 20 mass % or less.
[0048] The ratio of the thickness of the first region in the thickness of the crystallized indium tin composite oxide film is, for example, more than 50%, preferably more than 70%, more preferably more than 80%, and further preferably more than 90%. When the ratio of the thickness of the first region is greater than the above lower limit, the ratio of tin oxide in the crystallized indium tin composite oxide film can be increased, and thus the surface resistance of the crystallized indium tin composite oxide film can be sufficiently reduced. The ratio of the thickness of the first region in the thickness of the crystallized indium tin composite oxide film is, for example, less than 99%, preferably less than 97%.
[0049] The proportion of tin oxide in the second region is, for example, less than 8% by mass, preferably 7% by mass or less, more preferably 5% by mass or less, further preferably 4% by mass or less, and is, for example, 1% by mass or more, preferably 2% by mass or more, more preferably 3% by mass or more.
[0050] The ratio of the proportion of tin oxide in the first region to the proportion of tin oxide in the second region (proportion of tin oxide in the first region / proportion of tin oxide in the second region) is, for example, 1.5 or more, preferably 2 or more, more preferably 2.5 or more, and, for example, 5 or less, preferably 4 or less.
[0051] The concentration of tin oxide in the crystallized indium tin composite oxide film, the first region, and the second region is measured by X-ray photoelectron spectroscopy. Alternatively, the content ratio of tin oxide can also be estimated based on the composition (known) of the target used when forming the amorphous indium tin composite oxide film by sputtering.
[0052] The surface resistance of the crystallized indium tin composite oxide film is, for example, 60Ω / □ or less, preferably 50Ω / □ or less, more preferably 45Ω / □ or less, further preferably 40Ω / □ or less, particularly preferably 30Ω / □ or less, and most preferably 20Ω / □ or less.
[0053] When the surface resistance of the crystallized indium tin composite oxide film is not more than the above upper limit, when the crystallized indium tin composite oxide film is patterned and used as an electrode, excellent electrical characteristics can be expressed.
[0054] The lower limit of the surface resistance of the crystallized indium tin composite oxide film is not particularly limited. For example, the surface resistance of the crystallized indium tin composite oxide film is usually more than 0Ω / □, and is 1Ω / □ or more. The surface resistance of the crystallized indium tin composite oxide film is measured by a four-terminal method.
[0055] It should be noted that the arithmetic mean roughness Ra of the other side in the thickness direction of the crystallized indium tin composite oxide film is the same as the arithmetic mean roughness Ra of the other side in the thickness direction of the transparent film substrate, for example, because the other side in the thickness direction of the crystallized indium tin composite oxide film closely follows the one side in the thickness direction of the transparent film substrate described below. Specifically, the arithmetic mean roughness Ra of the other side in the thickness direction of the crystallized indium tin composite oxide film is, for example, 2 nm or less, preferably 1 nm or less, more preferably 0.75 nm or less, further preferably 0.5 nm or less, and, for example, 0.001 nm or more.
[0056] [Transparent conductive film]
[0057] Next, refer to Figure 1 A transparent conductive thin film including the above-mentioned crystallized indium tin composite oxide film will be described.
[0058] The transparent conductive film 3 has a film shape extending in the plane direction. The transparent conductive film 3 includes a transparent film substrate 2 and a crystallized indium tin composite oxide film 1 in this order toward one side in the thickness direction. The transparent conductive film 3 includes a transparent film substrate 2 and a crystallized indium tin composite oxide film 1 disposed on one surface in the thickness direction of the transparent film substrate 2. Preferably, the transparent conductive film 3 includes only the transparent film substrate 2 and the crystallized indium tin composite oxide film 1.
[0059] The transparent film substrate 2 forms the outer shape of the transparent conductive film 3. The transparent film substrate 2 is transparent. For example, the transparent film substrate 2 includes, in order toward one side in the thickness direction: an anti-blocking layer 5, a transparent film 6, a hard coating layer 7, and an optical adjustment layer 8. The transparent film substrate 2 includes: an anti-blocking layer 5, a transparent film 6 disposed on one surface in the thickness direction of the anti-blocking layer 5, a hard coating layer 7 disposed on one surface in the thickness direction of the transparent film 6, and an optical adjustment layer 8 disposed on one surface in the thickness direction of the hard coating layer 7. Preferably, the transparent film substrate 2 includes only the anti-blocking layer 5, the transparent film 6, the hard coating layer 7, and the optical adjustment layer 8.
[0060] The anti-adhesion layer 5 imparts anti-adhesion properties to each surface of a plurality of transparent conductive films 3 in contact with each other when the transparent conductive film 3 is stacked in the thickness direction. The material of the anti-adhesion layer 5 is, for example, an anti-adhesion composition. As the anti-adhesion composition, for example, a mixture described in Japanese Patent Gazette No. 2016-179686 can be cited. The mixture contains, for example, a resin (binder resin) such as an acrylic resin and contains inorganic and / or organic particles (preferably organic particles such as polystyrene). The thickness of the anti-adhesion layer 5 is, for example, more than 0.1 μm, and, for example, less than 10 μm.
[0061] The transparent film 6 is an essential layer in the transparent film substrate 2. The transparent film 6 is a transparent substrate for ensuring the mechanical strength of the transparent conductive film 3. The transparent film 6 has a film shape and extends in the surface direction. The transparent film 6 is in contact with one surface in the thickness direction of the anti-adhesion layer 5. As the material of the transparent film 6, for example, resins such as cycloolefin resin (COP) and polyester resin (polyethylene terephthalate (PET) etc.) can be listed. Preferably, cycloolefin resin can be listed. In addition, the transparent film 6 has isotropy or birefringence. The transparent film substrate 2 preferably has isotropy. The birefringence in the in-plane direction of the transparent film substrate 2 is, for example, less than 100, preferably less than 50, and, for example, more than 0. The thickness of the transparent film 6 is, for example, more than 10μm, and, for example, less than 100μm.
[0062] The hard coating layer 7 is a scratch protection layer for preventing the transparent conductive film 3 from being scratched. The hard coating layer 7 is in contact with one surface of the transparent film 6 in the thickness direction. The material of the hard coating layer 7 is, for example, a hard coating composition. As the hard coating composition, for example, a mixture described in Japanese Patent Publication No. 2016-179686 can be cited. The mixture contains, for example, a resin (binder resin) such as an acrylic resin and a urethane resin. The thickness of the hard coating layer 7 is, for example, greater than 0.1 μm, and, for example, less than 10 μm.
[0063] The optical adjustment layer 8 is a layer that suppresses the visibility of the pattern formed by the crystallized indium tin composite oxide film 1 and adjusts the optical properties (specifically, the refractive index) of the transparent conductive film 3. The optical adjustment layer 8 is in contact with one surface in the thickness direction of the hard coating layer 7. The material of the optical adjustment layer 8 is, for example, an optical adjustment composition. As an optical adjustment composition, for example, a mixture described in Japanese Patent Gazette No. 2016-179686 can be listed. The mixture contains, for example, a resin (binder resin) such as an acrylic resin and contains inorganic and / or organic particles (preferably inorganic particles such as zirconium oxide). The thickness of the optical adjustment layer 8 is, for example, greater than 0.05 μm, and, for example, less than 1 μm.
[0064] The arithmetic mean roughness Ra of one surface in the thickness direction of the optical adjustment layer 8 is, for example, 2 nm or less, preferably 1 nm or less, more preferably 0.75 nm or less, further preferably 0.5 nm or less, and, for example, 0.001 nm or more. The arithmetic mean roughness Ra of one surface in the thickness direction of the optical adjustment layer 8 is determined according to JIS B0681-6 (2017).
[0065] The thickness of the transparent film substrate 2 is, for example, 10 μm or more, and, for example, 100 μm or less. The total light transmittance of the transparent film substrate 2 is, for example, 80% or more, preferably 90% or more, and, for example, 99% or less.
[0066] The arithmetic mean roughness Ra of one surface in the thickness direction of the transparent film substrate 2 is the same as the arithmetic mean roughness Ra of the above-mentioned optical adjustment layer 8 .
[0067] When the arithmetic mean roughness Ra of one surface in the thickness direction of the transparent film substrate 2 is below the above upper limit, when the amorphous indium tin composite oxide film is heated to form the crystallized indium tin composite oxide film 1, the growth of crystal grains from the other surface in the thickness direction of the amorphous indium tin composite oxide film, which is in contact with the one surface in the thickness direction of the transparent film substrate 2, toward one side in the thickness direction can be promoted. Therefore, the average grain size of the crystal grains can be increased.
[0068] The crystallized indium tin composite oxide film 1 is in contact with one surface in the thickness direction of the transparent film substrate 2. One surface in the thickness direction of the crystallized indium tin composite oxide film 1 is exposed toward one side in the thickness direction. The other surface in the thickness direction of the crystallized indium tin composite oxide film 1 is in close contact (contact) with one surface in the thickness direction of the transparent film substrate 2. The arithmetic mean roughness Ra of the other surface in the thickness direction of the crystallized indium tin composite oxide film 1 is as described above, for example, 2 nm or less, preferably 1 nm or less, more preferably 0.75 nm or less, further preferably 0.5 nm or less, and for example, 0.001 nm or more.
[0069] The thickness of the transparent conductive film 3 is, for example, 15 μm or more, and, for example, 120 μm or less. The total light transmittance of the transparent conductive film 3 is, for example, 80% or more, preferably 90% or more, and, for example, 99% or less.
[0070] [Method for producing a transparent conductive film]
[0071] Next, a method for producing the transparent conductive film will be described.
[0072] The method for producing the transparent conductive film 3 comprises: a first step of sputtering one surface in the thickness direction of the transparent film substrate 2 to form an amorphous indium tin composite oxide film; and a second step of heating the amorphous indium tin composite oxide film to form a crystallized indium tin composite oxide film 1. In addition, in this production method, each layer is sequentially arranged by, for example, a roll-to-roll method.
[0073] In the first step, first, a transparent film substrate 2 is prepared.
[0074] For example, a transparent film 6 is prepared. Next, a hard coat layer 7 , an anti-blocking layer 5 , and an optical adjustment layer 8 are disposed on the transparent film 6 .
[0075] Specifically, first, a dilution of a hard coating composition and a dilution of an anti-blocking composition are applied to both sides of the transparent film 6 in the thickness direction, and then dried, and then the hard coating composition and the anti-blocking composition are cured by ultraviolet irradiation. Thus, a hard coating layer 7 and an anti-blocking layer 5 are formed on both sides of the transparent film 6 in the thickness direction. Thereafter, a dilution of an optical adjustment composition is applied to one side of the hard coating layer 7 in the thickness direction, and then dried, and then the optical adjustment composition is cured by ultraviolet irradiation. Thus, an optical adjustment layer 8 is formed. Thus, a transparent film substrate 2 is prepared, which is a laminated film having an anti-blocking layer 5, a transparent film 6, a hard coating layer 7, and an optical adjustment layer 8 in sequence toward one side in the thickness direction.
[0076] Next, in the first step, sputtering is performed on one surface in the thickness direction of the transparent film substrate 2. Specifically, in a sputtering device, one surface in the thickness direction of the transparent film substrate 2 is placed opposite to a target containing an indium tin composite oxide, and sputtering is performed in the presence of an inert gas. At this time, in addition to the above-mentioned inert gas, a reactive gas such as oxygen may also be present.
[0077] As the inert gas, for example, rare gases such as argon gas can be cited. The partial pressure of the inert gas in the sputtering device is, for example, 0.1 Pa or more, preferably 0.3 Pa or more, more preferably 0.5 Pa or more, and further preferably 0.55 Pa or more, and, for example, 10 Pa or less. When the partial pressure of the inert gas is above the above lower limit, the energy of the atoms of the inert gas in sputtering becomes lower. In this way, the amorphous indium tin composite oxide film can suppress the absorption of atoms of the inert gas. As a result, the growth of the crystal grains can be promoted. Thus, the average particle size of the crystal grains can be increased.
[0078] The pressure in the sputtering device is the total pressure of the partial pressure of the inert gas and the partial pressure of the reactive gas.
[0079] It should be noted that the first target and the second target having different tin oxide concentrations may be sequentially arranged in the sputtering device along the conveying direction of the transparent film substrate 2. The material of the first target is, for example, ITO (SnO 2 Concentration: 8 mass % or more). The material of the second target is, for example, ITO (SnO 2 Concentration: less than 8% by mass).
[0080] By the above-described sputtering, an amorphous indium tin composite oxide film is formed on one surface of the transparent film substrate 2 in the thickness direction.
[0081] It should be noted that when the amorphous indium tin composite oxide film is formed by sputtering using the first target and the second target, the amorphous indium tin composite oxide film has a first amorphous layer and a second amorphous layer having different tin oxide concentrations in sequence toward one side in the thickness direction. The materials of the first amorphous layer and the second amorphous layer are the same as those of the first target and the second target. Specifically, the SnO in the ITO of the first amorphous layer is 2 The concentration is, for example, 8 mass % or more. 2 The concentration is, for example, less than 8% by mass.
[0082] The ratio of the thickness of the first amorphous layer to the thickness of the amorphous indium tin composite oxide film is, for example, more than 50%, preferably more than 70%, more preferably more than 80%, and further preferably more than 90%. The ratio of the thickness of the first amorphous layer to the thickness of the crystallized indium tin composite oxide film is, for example, less than 99%, preferably less than 97%.
[0083] This amorphous indium tin composite oxide film has not yet been crystallized, that is, it is not the crystallized indium tin composite oxide film of the present invention. The amorphous indium tin composite oxide film is a precursor film (intermediate material) for obtaining a crystallized indium tin composite oxide film.
[0084] In this way, an amorphous laminated thin film including the transparent film substrate 2 and the amorphous indium tin composite oxide film is obtained.
[0085] Thereafter, in the second step, the amorphous laminated thin film is heated. For example, the amorphous indium tin composite oxide film is heated using a heating device such as an infrared heater or an oven.
[0086] The heating conditions are not particularly limited. The heating temperature is, for example, 90° C. or more, preferably 110° C. or more, and for example, 160° C. or less, preferably 140° C. or less. The heating time is, for example, 30 minutes or more, more preferably 60 minutes or more, and for example, 5 hours or less, preferably 3 hours or less.
[0087] Therefore, if Figure 1 As shown, the amorphous indium tin composite oxide layer is crystallized to form a crystallized indium tin composite oxide film 1 including a plurality of crystal grains.
[0088] When the amorphous indium tin composite oxide film includes a first amorphous layer and a second amorphous layer, the crystallized indium tin composite oxide film 1 includes a first region 11 and a second region 12 corresponding to the first amorphous layer and the second amorphous layer, respectively.
[0089] As described above, the crystallized indium tin composite oxide film 1 has a thickness of 35 nm or more and contains crystal grains having an average grain size of 110 nm or more.
[0090] In this way, the transparent conductive thin film 3 including the transparent film substrate 2 and the crystallized indium tin composite oxide film 1 is manufactured.
[0091] Thereafter, the transparent conductive thin film 3 is patterned into the crystallized indium tin composite oxide film 1 by, for example, etching, etc. The patterned crystallized indium tin composite oxide film 1 is used for an electrode of a touch panel (touch sensor) or the like.
[0092] Furthermore, the crystallized indium tin composite oxide film 1 has a thickness of 35 nm or more and thus has a low surface resistance.
[0093] In addition, the crystallized indium tin composite oxide film includes crystal grains having a large average grain size of 110 nm or more, and therefore has excellent chemical resistance.
[0094] Therefore, the crystallized indium tin composite oxide film 1 of the transparent conductive thin film 3 has excellent chemical resistance.
[0095] Furthermore, since the crystallized indium tin composite oxide film 1 includes the first region 11 in which the ratio of tin oxide is 8 mass % or more, the surface resistance of the crystallized indium tin composite oxide film 1 can be reduced.
[0096] Furthermore, since the transparent conductive thin film 3 includes the above-mentioned crystallized indium tin composite oxide film 1, it has low surface resistance and excellent chemical resistance.
[0097] In addition, in the transparent conductive film 3, when one surface in the thickness direction of the transparent film substrate 2 has a small arithmetic mean roughness Ra of 1.0 nm or less, the hindrance of the crystal growth of the amorphous indium tin composite oxide film arranged on one surface in the thickness direction of the transparent film substrate 2 is suppressed, so that crystal grains with a large average particle size can be formed in the crystallized indium tin composite oxide film 1. As a result, the transparent conductive film has excellent chemical resistance.
[0098] In the first step of the method for producing the transparent conductive thin film 3, when sputtering is performed in the presence of an inert gas having a partial pressure of 0.4 Pa or more, crystal grains having a large average particle size can be formed in the crystallized indium tin composite oxide film 1. As a result, a transparent conductive thin film 3 having a crystallized indium tin composite oxide film 1 having excellent chemical resistance can be produced.
[0099] Modifications
[0100] In the modification, the same reference numerals are used for the same components and steps as those in the first embodiment, and detailed description thereof is omitted. In addition, the modification can exert the same effects as those in the first embodiment unless otherwise specified. Furthermore, the first embodiment and its modification can be appropriately combined.
[0101] The crystallized indium tin composite oxide film may not contain the second region in which the proportion of tin oxide is less than 8 mass %, and may include only the first region in which the proportion of tin oxide is 8 mass % or more.
[0102] The transparent film substrate 2 is not particularly limited as long as it includes the transparent film 6. The present invention includes, for example, a first embodiment in which the transparent film substrate 2 includes only the transparent film 6, a second embodiment in which the transparent film substrate 2 includes the transparent film 6 and one layer selected from the group consisting of the anti-blocking layer 5, the hard coating layer 7, and the optical adjustment layer 8 (a total of two layers), and a third embodiment in which the transparent film substrate 2 includes the transparent film 6 and two layers selected from the group consisting of the anti-blocking layer 5, the hard coating layer 7, and the optical adjustment layer 8 (a total of three layers).
[0103] As an example of the third method (full 3-layer structure), Figure 2 As shown, the transparent film substrate 2 does not have a hard coating layer 7 (see Figure 1 ), and only has an anti-adhesion layer 5, a transparent film 6 and an optical adjustment layer 8.
[0104] Example
[0105] Embodiment and comparative example are shown below, and the present invention is described in more detail.It should be noted that the present invention is not subject to any limitation of embodiment and comparative example.In addition, the specific numerical values such as the blending ratio (containing ratio), physical property value, parameter used in the following record can be replaced with the upper limit (defined as the numerical value of "below", "not enough") or the lower limit (defined as the numerical value of "above", "exceeding") of the blending ratio (containing ratio), physical property value, parameter corresponding to them recorded in the above-mentioned "specific embodiments".
[0106] Example 1
[0107] First, a transparent film 6 made of a cycloolefin resin (COP film, thickness 40 μm, manufactured by Zeon Corporation, “ZEONOR” (registered trademark), in-plane birefringence 0.0001) was prepared.
[0108] Next, a diluted solution of a hard coating composition containing a binder resin (urethane multifunctional polyacrylate, trade name "UNIDIC", manufactured by DIC Corporation) is applied to one side in the thickness direction of the transparent film 6, and a diluted solution of an anti-blocking composition containing a binder resin (urethane multifunctional polyacrylate, trade name "UNIDIC", manufactured by DIC Corporation) and particles (cross-linked acrylic styrene resin particles, trade name "SSX105", diameter 3 μm, manufactured by Sekisui Jushi Co., Ltd.) is applied to the other side in the thickness direction of the transparent film 6, and then, after drying, ultraviolet rays are irradiated to both sides in the thickness direction of the transparent film 6 to cure the hard coating composition and the anti-blocking composition. Thus, a hard coating layer 7 with a thickness of 1 μm is formed on one side of the transparent film 6, and an anti-blocking layer 5 with a thickness of 1 μm is formed on the other side in the thickness direction of the transparent film 6.
[0109] Next, a diluted solution of an optical adjustment composition containing zirconium oxide particles and an ultraviolet curable resin (acrylic resin) ("OPSTAR Z7412", manufactured by JSR Corporation, with a refractive index of 1.62) was applied to one surface in the thickness direction of the hard coating layer, dried at 80°C for 3 minutes, and then irradiated with ultraviolet light. Thus, an optical adjustment layer 8 with a thickness of 0.1 μm was formed on one surface in the thickness direction of the hard coating layer 7. Thus, a laminated film including an anti-blocking layer 5, a transparent film 6, a hard coating layer 7, and an optical adjustment layer 8 was obtained as a transparent film substrate 2.
[0110] Thereafter, an amorphous indium tin composite oxide layer 1 having a thickness of 39.7 nm was formed on one surface of the optical adjustment layer 8 in the thickness direction by sputtering.
[0111] Specifically, first, a first target including ITO having a tin oxide concentration of 10% by weight and a second target including ITO having a tin oxide concentration of 3.3% by weight are sequentially arranged in a sputtering device from the upstream side to the downstream side in the conveying direction of the transparent film substrate 2. Then, sputtering is performed in such a manner that the ratio of the thickness of the first amorphous layer and the ratio of the thickness of the second amorphous layer in the amorphous indium tin composite oxide film are 95% and 5%, respectively. It should be noted that the amorphous indium tin composite oxide film sequentially includes the first amorphous layer (tin oxide concentration of 10% by weight) and the second amorphous layer (tin oxide concentration of 3.3% by weight) toward one side in the thickness direction.
[0112] The argon gas flow rate during sputtering was adjusted to adjust the argon gas partial pressure in the sputtering device to 0.35 Pa. The pressure in the sputtering device was 0.42 Pa.
[0113] In this way, an amorphous multilayer film including the anti-adhesion layer 5, the transparent film 6, the hard coat layer 7, the optical adjustment layer 8, and the amorphous indium tin composite oxide layer in this order is produced.
[0114] Thereafter, the amorphous laminated thin film was heated at 130° C. for 90 minutes to crystallize the amorphous indium tin composite oxide layer, thereby preparing a crystallized indium tin composite oxide film 1 .
[0115] Thus, manufacturing Figure 1 The transparent conductive film 3 shown includes an anti-blocking layer 5 , a transparent film 6 , a hard coat layer 7 , an optical adjustment layer 8 , and a crystallized indium tin composite oxide film 1 .
[0116] Furthermore, the crystallized indium tin composite oxide film 1 includes a first region 11 and a second region 12 derived from the first amorphous layer and the second amorphous layer, respectively.
[0117] Comparative Example 1-Comparative Example 2
[0118] The same treatment as in Example 1 was carried out except that the formulation was changed as described in Table 1.
[0119] Example 2
[0120] The same treatment as in Example 1 was carried out except that an optical adjustment layer 8 having a thickness of 0.7 μm was formed instead of the hard coat layer 7 and the optical adjustment layer 8 in Example 1.
[0121] That is, Figure 2 As shown, the transparent film substrate 2 includes an anti-blocking layer 5 , a transparent film 6 , and an optical adjustment layer 8 in this order, but does not include a hard coating layer 7 .
[0122] It should be noted that, for the optical adjustment layer 8, a diluted solution of an optical adjustment composition containing zirconium oxide particles, silicon dioxide particles and an ultraviolet curable resin (acrylic resin) ("TYZ72-A12" manufactured by TOYOCHEM CO., LTD., refractive index 1.72) is applied to one surface in the thickness direction of the transparent film 6, dried at 80°C for 3 minutes, and then irradiated with ultraviolet rays.
[0123] Embodiment 3 to Embodiment 6
[0124] The same treatment as in Example 2 was carried out except that the formulation was changed as described in Table 1.
[0125] Example 7
[0126] The process was carried out in the same manner as in Example 2 except that the sputtering device was not equipped with the second target and the recipe was changed as described in Table 1.
[0127] The amorphous indium tin composite oxide film does not include the second amorphous layer but includes the first amorphous layer. The crystallized indium tin composite oxide film 1 does not include the second region 12 but includes the first region 11 .
[0128] <Evaluation>
[0129] The following items were evaluated. The results are shown in Table 1.
[0130] [Average grain size]
[0131] One surface in the thickness direction of the crystallized indium tin composite oxide film 1 of the transparent conductive thin film 3 in each of the examples and comparative examples was observed by SEM.
[0132] The multiple polygonal particles confirmed by SEM observation are defined as ITO grains. Then, the area of each of the multiple grains is calculated. The average value of the square root of the value obtained by dividing the area of each grain by pi (π) is calculated as the average grain size of the grains.
[0133] By SEM observation, a field of view image of 1500nm in length and 1500nm in width is obtained. In this field of view image, the grain boundaries separating the grains are determined. Based on this, the area of multiple grains is calculated. The square root of the value obtained by dividing the area of 1 grain by pi (π) is twice the value approximated as the particle size of 1 grain. It should be noted that grains with a particle size of less than 20nm are excluded from the calculation of the average value.
[0134] That is, only the areas and numbers of multiple grains with a grain size of 20 nm or more and which do not overflow from the field of view image (that is, the entire grain is completely contained in the field of view image) are used to calculate the average value, and the resulting average value is taken as the "average grain size of the grains".
[0135] The apparatus and measurement conditions are as follows.
[0136] SEM equipment: Scanning electron microscope SU8020 manufactured by Hitachi High-Technologies
[0137] Accelerating voltage: 0.8 kV
[0138] The image processing diagram of the SEM photograph of Example 1 is shown in Figure 3 A, the image processing diagram of the SEM photograph of Comparative Example 2 is shown in Figure 3 B.
[0139] [Surface resistance of crystallized indium tin composite oxide film]
[0140] The surface resistance of the crystallized indium tin composite oxide film 1 of the transparent conductive thin film 3 in each example and each comparative example was measured by a four-probe method. The surface resistance was evaluated based on the following criteria.
[0141] ◎: Surface resistance is 40Ω / □ or less.
[0142] ○: The surface resistance is 60Ω / □ or less and exceeds 40Ω / □.
[0143] ×: Surface resistance exceeds 60Ω / □.
[0144] [Chemical resistance of crystallized indium tin composite oxide film]
[0145] A cutter was used to make a scratch on one surface in the thickness direction of the crystallized indium tin composite oxide film 1 of the transparent conductive thin film 3 in each of the examples and the comparative examples.
[0146] Thereafter, the transparent conductive film 3 was immersed in a 16 mass % ammonium persulfate aqueous solution at 20° C. for 5 minutes, and then immersed in a 3 mass % potassium hydroxide aqueous solution at 30° C. for 20 minutes.
[0147] Thereafter, scratches were observed with an optical microscope, and chemical resistance was evaluated based on the following criteria.
[0148] ×: A plurality of crack portions extending from the scratch were observed.
[0149] ○: The above-mentioned crack portion was observed very slightly.
[0150] ⊚: The above-mentioned crack portion was not observed.
[0151] [Arithmetic mean roughness Ra of transparent film substrate]
[0152] According to JIS B0681-6 (2017), the arithmetic mean roughness Ra of one surface in the thickness direction of the transparent conductive thin film 3 before forming the amorphous indium tin composite oxide film, that is, the transparent film substrate 2, was determined using an atomic force microscope (Nonoscope IV manufactured by Digital Instruments). A range of 1 μm×1 μm in one surface in the thickness direction of the transparent film substrate 2 was observed using an atomic force microscope (field of view image).
[0153] [Content Ratio of Tin Oxide in Crystallized Indium Tin Composite Oxide Film]
[0154] First, the content ratio of tin oxide in the amorphous indium tin composite oxide film is determined based on the tin oxide concentrations in the first and second targets and the ratio of the thickness of the first amorphous layer to the thickness of the second amorphous layer in the amorphous indium tin composite oxide film.
[0155] Assuming that there is no change in the concentration of tin oxide during the transition from the amorphous indium tin composite oxide film to the crystallized indium tin composite oxide film, the content of tin oxide in the amorphous indium tin composite oxide film is estimated as the content of tin oxide in the crystallized indium tin composite oxide film.
[0156] [Table 1]
[0157]
[0158] It should be noted that the above invention is provided as an exemplary embodiment of the present invention, but this is merely an illustration and is not to be construed as limiting. Modifications of the present invention that are obvious to a person skilled in the art are included in the above claims.
[0159] Industrial Applicability
[0160] The transparent conductive thin film may include a crystallized indium tin composite oxide film.
[0161] Description of Reference Numerals
[0162] 1 Crystallized Indium Tin Oxide Film
[0163] 2 Transparent film substrate
[0164] 3 Transparent conductive film
[0165] 9 Grains
[0166] 11 Area 1
Claims
1. A transparent conductive film, characterized in that: A method of manufacturing a transparent film substrate comprising: a transparent film substrate; and a crystallized indium tin composite oxide film disposed on one surface in a thickness direction of the transparent film substrate, wherein the one surface in the thickness direction of the transparent film substrate has an arithmetic mean roughness Ra of 1.0 nm or less, The crystallized indium tin composite oxide film has a thickness of 35 nm or more, The crystallized indium tin composite oxide film includes crystal grains having an average particle size of 110 nm or more.
2. The transparent conductive film according to claim 1, characterized in that: The crystallized indium tin composite oxide film includes a region in which the ratio of tin oxide is 8 mass % or more.
3. A method for producing a transparent conductive film, characterized in that: A method for producing the transparent conductive film according to claim 1, comprising: In a first step, sputtering is performed on one surface in the thickness direction of the transparent film substrate to form an amorphous indium tin composite oxide film; and In a second step, the amorphous indium tin composite oxide film is heated to form a crystallized indium tin composite oxide film. In the first step, sputtering is performed in the presence of an inert gas having a partial pressure of 0.4 Pa or more.
4. A method for producing a transparent conductive film, characterized in that: A method for producing the transparent conductive film according to claim 2, comprising: In a first step, sputtering is performed on one surface in the thickness direction of the transparent film substrate to form an amorphous indium tin composite oxide film; and In a second step, the amorphous indium tin composite oxide film is heated to form a crystallized indium tin composite oxide film. In the first step, sputtering is performed in the presence of an inert gas having a partial pressure of 0.4 Pa or more.
Citation Information
Patent Citations
Mobile wireless apparatus and antenna element selecting method of mobile wireless apparatus
JP2010028275A
Transparent conductive film and method for manufacturing the same
JP2016179686A
Film with transparent conductive film, base board for display composed of this film with transparent conductive film, display, and organic el element
JP2008021605A
Method and apparatus for forming ITO transparent conductive film
JP2011214043A